Web-Based Sales System Using the Cash-Basic Method - Endaryati, Eni; Vivi Kumalasari Subroto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
Sales are important transactions for companies or agencies because they are the main source of income used to carry out operational activities. In making sales, data processing procedures are needed which are arranged in a certain sequence, which in the accounting system is called a sales procedure. By using the Cash Basis method, companies do not need to make reserves for uncollected cash and can display actual cash position reports. A sales system that will make it easier to manage sales transactions and present sales reports quickly and validly. Web-based applications can be used to manage finances, business and services. Makes it easier to present sales reports both daily and monthly and can minimize errors when information is generated. Good management of information systems will increase efficiency and productivity in decision making by management